Kinematics of the diffuse intragroup and intracluster light in groups and clusters of galaxies in the local universe within 100 Mpc distance - Arnaboldi, Magda; Gerhard, Ortwin (Frontiers in Astronomy and Space Sciences, 2022)
Nearly all intragroup (IGL) and intracluster light (ICL) comes from stars that are not bound to any single galaxy but were formed in galaxies and later unbound from them. In this review we focus on the physical properties–phase space properties, metallicity and age distribution–of the ICL and IGL components of the groups and clusters in the local universe, within 100 Mpc distance. Kinematic–information on these very low surface brightness structures mostly comes from discrete tracers such as planetary nebulae and globular clusters, showing highly unrelaxed velocity distributions. Cosmological hydrodynamical simulations provide key predictions for the dynamical state of IGL and ICL and find that most IC stars are dissolved from galaxies that subsequently merge with the central galaxy. The increase of the measured velocity dispersion with radius in the outer halos of bright galaxies is a physical feature that makes it possible to identify IGL and ICL components. In the local groups and clusters, IGL and ICL are located in the dense regions of these structures. Their light fractions relative to the total luminosity of the satellite galaxies in a given group or cluster are between a few to ten percent, significantly lower than the average values in more evolved, more distant clusters. IGL and ICL in the Leo I and M49 groups, and the Virgo cluster core around M87, has been found to arise from mostly old (≥10 Gyr) metal-poor ([Fe/H] <-1.0) stars of low-mass progenitor galaxies. New imaging facilities such as LSST, Euclid, and the “big eyes’’ on the sky–ELT and JWST with their advanced instrumentation–promise to greatly increase our knowledge of the progenitors of the IGL and ICL stars, their ages, metal content, masses and evolution, there by increasing our understanding of this enigmatic component.